2017
DOI: 10.1111/aec.12532
|View full text |Cite
|
Sign up to set email alerts
|

Body size variation and sexual size dimorphism across climatic gradients in the widespread treefrog Scinax fuscovarius (Anura, Hylidae)

Abstract: Variation in body size represents one of the crucial raw materials for evolution. However, at present, it is still being debated what is the main factor affecting body size or if the final body size is the consequence of several factors acting synergistically. To evaluate this, widespread species seem to be suitable models because the different populations occur along a geographical gradient and under contrasted climatic and environmental conditions. Here we describe the spatial pattern of variation in body si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…First, intraspecific amphibian body size has been shown to increase with decreasing temperatures, consistent with the heat balance hypothesis which predicts a negative relationship between body size and measures of energy availability (Boaratti & Da Silva, 2015;Ficetola et al, 2010;Rivas et al, 2018), although this has been found to not always be the case (Goldberg et al, 2018;Guo et al, 2019). Second, several studies have shown that larger bodied animals are found in drier areas (Goldberg et al, 2018;Guo et al, 2019;Olalla-Tárraga et al, 2009) providing support for the water availability hypothesis which predicts that larger bodied animals are less prone to desiccation due to reduced surface-to-volume ratio. In contrast, the converse water availability hypothesis argues that body size is positively related to water availability such that larger animals will be found in areas with greater precipitation (Zug et al, 2001).…”
Section: Introductionmentioning
confidence: 54%
“…First, intraspecific amphibian body size has been shown to increase with decreasing temperatures, consistent with the heat balance hypothesis which predicts a negative relationship between body size and measures of energy availability (Boaratti & Da Silva, 2015;Ficetola et al, 2010;Rivas et al, 2018), although this has been found to not always be the case (Goldberg et al, 2018;Guo et al, 2019). Second, several studies have shown that larger bodied animals are found in drier areas (Goldberg et al, 2018;Guo et al, 2019;Olalla-Tárraga et al, 2009) providing support for the water availability hypothesis which predicts that larger bodied animals are less prone to desiccation due to reduced surface-to-volume ratio. In contrast, the converse water availability hypothesis argues that body size is positively related to water availability such that larger animals will be found in areas with greater precipitation (Zug et al, 2001).…”
Section: Introductionmentioning
confidence: 54%
“…An interspecific study in the Cerrado ecoregion also found a positive relationship between anurans’ body sizes and water deficit, with larger species inhabiting areas with higher water deficit (Olalla–Tárraga et al , 2009). At the intraspecific level, the same pattern was found in Dendropsopohus minutus (Oyamaguchi et al , 2016) and Scinax fuscovarius (Goldberg et al , 2017), whereas the inverse relationship was found in Boana faber and no relationship was found in Physalaemus cuvieri (Boaratti & da Silva, 2015). According to Gouveia et al (2019), increasing body size to avoid desiccation is a more effective strategy in small size anuran species, because a little increase of size in small species results in a much larger water economy in comparison to large size ones, for which investing in mechanisms to increase skin resistance may be a better strategy.…”
Section: Discussionmentioning
confidence: 70%
“…This hypothesis is based on the association among the activity of amphibians and high levels of water availability (Ficetola et al , 2010) and contradicts the water conservation hypothesis. A large body in amphibians is advantageous in both, dry climates and also in wet areas (Trochet et al , 2019); however, in this specific case, the analyses support a clearly stronger influence of seasonality over body sizes (Table 1) being in concordance with other Neotropical species (Oyamaguchi et al , 2016; Goldberg et al , 2017).…”
Section: Discussionmentioning
confidence: 77%
“…Larger body size in such species is in accordance with the 'starvation hypothesis' that predicts that greater mass is positively correlated to seasonality and periods of low resource availability (Lundberg 1986), because larger individuals can persist through low-resource events by having greater energy stores and typically more efficient metabolism owing to positive allometry. The starvation hypothesis has received recent support in multiple amphibian taxa, where body size is positively related to extended inactivity (Valenzuela-Sánchez et al 2015) and increased precipitation seasonality (Goldberg et al 2018).…”
Section: Discussionmentioning
confidence: 99%